Defend The Country: Generation Z Perspective - et. al., Sri Astuti Pratminingsih, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Implementing the concept of state defense is now increasingly broad, not only facing threats militarily but also non-military with various variations. Currently, 28% of Indonesia's population is Generation Z, namely those born between 1997 - 2012. As the nation's next-generation, Generation Z must increasingly understand that the various challenges and opportunities that will be faced are different from the previous generation. Based on the study results, respondents stated that Generation Z needed insight and understanding of relevant state defense as a form of a contribution to love for the country. Respondents stated that so far, the concept of state defense is more perceived as attitudes and actions related to "physical" or "war" in the true sense. Therefore, this paper hopes to provide insight into the importance of continuous understanding from all stakeholders by inviting and involving Generation Z to contribute and work for hand in hand for the Indonesian nation's progress. The Covid-19 pandemic is a momentum to strengthen cooperation, collaboration, and tolerance so that they can rise together for the Unitary State of the Republic of Indonesia.